Investigation of hardware for adaptive minimal mean square error filter using verilog HDL - Wu, Lixin. (2008)
This report discusses the work done on implementing the adaptive Minimal Mean Square Error (MMSE) filter in C and Verilog HDL. The algorithm of adaptive MMSE filter is first introduced, which estimates the original signal in the sense of local linear minimal mean square error. The filter implementation in C for VirtualDub is next discussed. Experimental results on video signals show that the filter is very effective in removing Gaussian noise. Its weakness on impulsive noise is also demonstrated. A proposal has been suggested to improve its performance on impulsive noise, and evaluation results are promising. Next is the introduction of the filter implementation in Verilog HDL. The simulation results obtained from Active HDL environment are finally discussed.